Telerobotic Manipulation of the Brachial Plexus - Garcia, Jose Carlos; Lebailly, Frederic; Mantovani, Gustavo; Mendonca, Leonardo Alves; Garcia, Jesely; Liverneaux, Philippe (Journal of Reconstructive Microsurgery, 2012)
Objective This study demonstrates the new technology of the robotic telesurgery on three brachial plexus reconstructions. We also discuss the implications, problems, and benefits of robotically assisted brachial plexus surgery.Methods After the first experimental experience in a cadaveric model, the authors performed three brachial plexus reconstructions. The surgery followed the traditional brachial plexus approach. From the moment that nervous sutures would be performed, the Da Vinci® (Intuitive Surgical™, Sunnyvale, CA) equipment was docked at the patients, positioned behind the patient's head, and the microsurgical steps were performed by using robotic telemanipulation.Results The first procedure was performed in a cadaver to gain experience and establish a surgical protocol by using the robot. In all the three living patients, the goals of the surgical procedure were achieved using the telerobotic manipulation.Conclusion Robot-assisted surgery allows performance of high-dexterity surgical operations with the help of robotic arms and it improves the surgery due to tremor filtration, motion scaling, and ergonomics. The benefit of using the robot on microsurgery was reached, but its entire potential was not realized because the instruments used on those first experimental and clinical cases were not specifically designed for microsurgery.
Keywords: brachial plexus; robotic microsurgery; robotic surgery